–2x + 5y = –19.....(1)
x – 3y = 10.....(2)
Multiply both sides of (2) by 2
x – 3y = 10
2(x – 3y) = 2*10
2x - 6y = 20.....(3)
Now add (1) and (3)
2x - 2x + 5y - 6y = -19 + 20
-y = 1
y = -1.....(4)
Substitute (4) in any equations. I choose (2)
x – 3y = 10
x - 3(-1) = 10
x + 3 = 10
x = 7
x = 7, y = -1 is the solution
2007-03-18 05:15:27
·
answer #1
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
x-3y=10
+3y . +3y
x=10+3y
-2(10+3y) +5y=-19
-20-6y+5y=-19
+20 . . . . .+20
-6y+5y=1
-y=1
y=-1
x-3(-1)=10
x+3=10
+-3 . +-3
x=7
-2(7)+5(-1)=-19
-14+-5=-19
-19=-19
y=-1 and x=7
Only added to both sides of equations.
2007-03-18 12:18:22
·
answer #2
·
answered by bmbougie 3
·
0⤊
0⤋
add both equations
-2x +5y = -19
+ x -3y = 10
--------------------
-x + 2y = -9
therefore, x = 2y +9
then you plug x into one of the equations
second equation = (2y+9) - 3y = 10
-y+9 = 10
-y = 1
y = -1
then you plug y into x=2y+9 to get x
x = 2(-1) + 9
x = 7
check your answers by plugging both x and y into the two original equations
x = 7 y = -1
-2(7) + 5(-1) = -19
-19 = -19
7 - 3(-1) = 10
10 = 10
2007-03-18 12:11:09
·
answer #3
·
answered by devildeb89 2
·
0⤊
0⤋
multiply the second equation by 2 and add the two equations
-2x+5y=-19
2x-6y=20
add them
-y=1
y=-1
substitute y with -1 in any equation
lets take the second one:
x-3(-1)=10
x+3=10
x=7
2007-03-18 12:03:22
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Multiply the second equation by 2
Add the two equations
Get y= -1
Substitute -1 for y in first equation
Get x = 7
2007-03-18 12:12:20
·
answer #5
·
answered by ? 5
·
0⤊
0⤋
-2x+5y= -19..........eq(i)
x-3y=10.................eq(ii)*2
2x-6y=20..................eq(iii)
Adding eq(i) to eq(iii),
-2x+5y= -19
2x-6y=20
we get,
-y=1
or, y= -1
putting the value of y in eq(ii), we get
x-3(-1)=10
x+3=10
x=10-3
x=7
Therefore, x=7 and y= -1
2007-03-18 12:04:23
·
answer #6
·
answered by Bubblez 3
·
0⤊
0⤋